1985
DOI: 10.3109/10641968509077221
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Patterns of Atrial Natriuretic Factor (ANF) By Culture Cardiocytes of Right and Left Atrium From Newborn and Adult RS

Abstract: Atrial cardiocytes from newborn (2-5 day old) and adult rats were cultured and the secretory patterns of atrial natriuretic factor (ANF) from isolated right and left atrial cells were investigated by radioimmunoassay. Newborn atrial cardiocytes from the left atrium consistently secreted larger amounts of ANF than those from the right with a peak on the 6th day and a decrease up to the 12th day. In contrast, adult atrial cardiocytes secreted much less ANF and this decreased to very low levels from the 3rd day u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Iwai and Inagami (7) and Kakar et al (13) have proposed that AT lb-R mediates endocrine function such as the secretion of aldosterone from the adrenal gland, and adrenocorticotropic hormone and prolactin from the pituitary gland, because of its localized distribution in the rat tissue. The cardiomyocytes secrete atrial natriuretic factor (ANF), whereas ANF granules are not present in cardiac fibroblasts (43,44). It has been reported that AngII directly stimulates ANF secretion from neonatal rat cardiomyocytes, but not from cardiac fibroblasts (43).…”
Section: Discussionmentioning
confidence: 99%
“…Iwai and Inagami (7) and Kakar et al (13) have proposed that AT lb-R mediates endocrine function such as the secretion of aldosterone from the adrenal gland, and adrenocorticotropic hormone and prolactin from the pituitary gland, because of its localized distribution in the rat tissue. The cardiomyocytes secrete atrial natriuretic factor (ANF), whereas ANF granules are not present in cardiac fibroblasts (43,44). It has been reported that AngII directly stimulates ANF secretion from neonatal rat cardiomyocytes, but not from cardiac fibroblasts (43).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of cRNA probes has been shown to give hybridization of higher specificity and sensitivity (35,36) than that obtained with other probe types. Rat atrial cultures have previously been used to investigate the biosynthesis and secretion of prepro-ANP (13,37,38). The present findings indicate the potential value of using cRNA probes and cardiac cultures to examine the regulation of ANP gene expression in atrial and nonatrial tissues.…”
Section: Discussionmentioning
confidence: 57%